The making of curriculum : collected essays - Goodson, Ivor. F. (London : The Falmer Press, 1995)
This is a new, updated version of Ivor Goodson's earlier work which explores A Number Of Aspects Of The "Invention" And Promotion Of So-Called "traditional" subjects. This edition has been extended and updated to include the National Curriculum
Includes bibliographical references and index.
Keywords: Education, Secondary -- Curricula -- History; Curriculum planning -- History; Curriculum change -- History